PEMANFAATAN LIMBAH KOTORAN HEWAN TERNAK SEBAGAI BIOGAS UNTUK KEPERLUAN RUMAH TANGGA DI KECAMATAN SIDEMEN KABUPATEN KARANGASEM BALI - Rukmi Sari Hartati; I W. Sukerayasa; I N.Suprapta Winaya; K.Amerta Yasa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2012)
In order to fulfill the need of society energy, especially in the rural area, the building of an energy storage in every village is compulsory. The energy storage should be built by utilizing the local energy potency source, be processed and utilize as the energy reservoir, resulting the self-sufficiently energy. This Community Service was done in Pungutan, Telun Wayah village, Sidemen Karangasem regency. The farmers group was given the illumination how to use and utilize the cattle-drops to be biogas. They were very interested in attending this activity and they hope it can be continued.